DOZ047.92: Oesophageal atresia: a multicenter retrospective study on surgical treatment and 1-year follow-up. (24th June 2019) - Vercauteren, C; Reusens, H; De Backer, A; Tambucci, R; Van Cauwenberge, S; Leyman, P; Ruppert, M; Demarche, M; Vervloessem, D; Matthyssens, L
Abstract: Introduction: No data are available on surgical management and outcomes of oesophageal atresia (OA) in Belgium. In collaboration with the Belgian Association of Paediatric Surgery (BELAPS) a retrospective study was organized to analyze data from children born with OA, with a 1-year follow-up. Materials and Methods: Out of 17 centers in Belgium, 10 participated in this study. A novel checklist to collect data from OA patients born between the 1st of January 2010 and the 1st of January 2015 was created. Gross type A, B, C and D OA were included. Results: One hundred children were included. Gross type C OA was seen in 86%. Associated malformations were present in 73%, most frequently cardiac malformations (52%). There was consensus regarding preoperative investigations, anastomotic technique, and transanastomotic tube placement. There was no consensus regarding genetic counseling, placement of a chest tube, and start of enteral feeding. There were six deaths in the first year of life. The majority of patients needed rehospitalization during the first year of life (85.9%) and there was a high occurrence of anastomotic strictures (51.6%). Conclusions: This is the first study about management and outcome of OA in Belgium. Although the 1-year survival rate is high (93.8%), these data illustrate that OA has an important morbidity. Multidisciplinary follow-up and prospective studies/registries with longer follow-up are needed.